Evaluation of User Experience in Translator Applications (Banjar-Indonesian and Indonesian-Banjar) Based on Mobile Augmented Reality Technology using the UX Honeycomb Method - Aulia Akhrian Syahidi; Herman Tolle (Journal of Games, Game Art, and Gamification, 2021)
The translator application from Banjar Language to Indonesian is called BandoAR and vice versa from Indonesian to Banjar Language which is called NdoBAR. Both applications utilize Mobile Augmented Reality technology with the Optical Character Recognition (OCR) Method for word recognition in the detected image. This application is recommended and used to help tourists visiting the city of Banjarmasin to be able to understand the language used by local people as a means of communication and for the general public who want to know the peculiarities of the Banjar language itself. The purpose of this study was to evaluate the user experience of the BandoAR and NdoBAR applications. The method used is UX Honeycomb, which has seven aspects to assess the user experience of an application. A total of 50 respondents were presented to assess the two applications. The results showed that the BandoAR application had an average UX Honeycomb value of 4.91 with a Very Strongly Agree predicate and for the NdoBAR application, an average value of UX Honeycomb was 4.89 with a Very Strongly Agree predicate. Both applications have fulfilled aspects of the user experience. However, we need some fixes for the shortcomings of both apps, to continue to improve interactions, better user experience, and other smart capabilities.